Genome‐wide association studies in a barley (Hordeum vulgare) diversity set reveal a limited number of loci for resistance to spot blotch (Bipolaris sorokiniana). (9th December 2019) - Novakazi, Fluturë; Afanasenko, Olga; Lashina, Nina; Platz, Gregory J.; Snowdon, Rod; Loskutov, Igor; Ordon, Frank
Abstract: Spot blotch caused by Bipolaris sorokiniana is an important disease in barley worldwide, causing considerable yield losses and reduced grain quality. In order to identify QTL conferring resistance to spot blotch, a highly diverse worldwide barley set comprising 449 accessions was phenotyped for seedling resistance with three isolates ( No 31, SH 15 and SB 61 ) and for adult plant resistance at two locations (Russia and Australia) in two years. Genotyping with the 50 k iSelect barley SNP genotyping chip yielded 33, 818 informative markers. Genome‐wide association studies (GWAS) using a compressed mixed linear model, including population structure and kinship, revealed 38 significant marker‐trait associations (MTA) for spot blotch resistance. The MTA corresponded to two major QTL on chromosomes 1H and 7H and a putative new minor QTL on chromosome 7H explaining between 2.79% and 13.67% of the phenotypic variance. A total of 10 and 14 high‐confidence genes were identified in the respective major QTL regions, seven of which have a predicted involvement in pathogen recognition or defence.